Analisis Kesan Emosional Pengguna Terhadap Desain Antarmuka Aplikasi Qpon Menggunakan Kansei Engineering Type 1 - Kanda M. Ishak; Muhamad Furqon; Putri Elsa Safira; Rahma Sabila (INTERNAL (Information System Journal), 2026)
This study analyzes users’ emotional impressions of the Qpon app’s interface design using the Kansei Engineering Type 1 method. Data were collected via a questionnaire involving 107 respondents who evaluated 10 kansei words across four interface pages: Home, Browse, Orders, and Account. Multivariate analysis included Cronbach’s Alpha reliability testing, Pearson Correlation Analysis, Factor Analysis (FA), and Partial Least Squares (PLS). The results indicate that the instrument has excellent reliability and that the visual design influences users’ interest in using the application. This study produced recommendations for interface design improvements to generate a positive user impression of the Qpon application interface.